Antioxidants protect against gingival overgrowth induced by cyclosporine A. (14th January 2021) - Chin, Yu‐Tang; Tu, Hsiao‐Pei; Lin, Chi‐Yu; Kuo, Po‐Jan; Chiu, Hsien‐Chung; Liu, Shao‐Hsien; Lee, Sheng‐Yang; Fu, Earl
Abstract: Objective: We investigated the importance of reactive oxygen species (ROS) on developing gingival overgrowth (GO) and then introduced the antioxidant strategy to prevent, or even reduce GO. Background: Gingival overgrowth is a common side effect of the patients receiving cyclosporine A (CsA), an immune suppressant. Although it has been broadly investigated, the exact pathogenesis of the induced GO is still uncertain. Methods: We cultured human primary gingival fibroblasts and used animal model of GO to investigate the ameliorative effects of antioxidants on CsA‐induced GO. To examine the CsA‐induced oxidative stress, associated genes and protein expression, and the overgrown gingiva of rats by using immunocytochemistry, confocal laser scanning microscopy, real‐time PCR, ELISA, gelatin zymography, gingival morphological, and immunohistochemical analysis. Results: We found for the first time that ROS was responsible for the CsA‐induced oxidative stress and TGF‐β1 expression in human primary gingival fibroblasts, as well as the GO of rats. The antioxidants (oxidative scavenger of vitamin E and an antioxidative enzyme inducer of hemin) ameliorated CsA‐induced pathological and morphological alterations of GO without affected the CsA‐suppressed il‐2 expression in rats. CsA‐induced oxidative stress, HO‐1, TGF‐β1, and type II EMT were also rescued by antioxidants treatment. Conclusions: We concluded that CsA repetitively stimulating the production of ROS is the cause of CsA‐GO which is ameliorated by treating antioxidants, including vitamin E and sulforaphane. Furthermore, the immunosuppressive effect of CsA is not interfered by antioxidant treatments in rats. This finding may thus help the clinician devise better prevention strategies in patients susceptible to GO.